Pengaruh Marketing Mix Terhadap Keputusan Konsumen Membeli Handphone Flexi Pada PT. Telekomunikasi Indonesia, Tbk Samarinda - -, Yeni Yulianawati (EKONOMIA, 2014)
Marketing Mix To Influence The Customers Decision To Buy Mobile Flexi At Pt Telecommunications Indonesia, Tbk Samarinda, Under The Guidance Of Mr. Mulyadi And Mrs. Eka Yudhyani.Research Conducted At Pt Telkom Samarinda Dahlia Road No 65 Samarinda. Research Purposes To Determine The Variable Product, Price, Promotion, And Distribution To The Consumers Decision To Buy Mobile Flexi At Pt Telecommunication Indonesia, Tbk Samarinda.Model Studies Of The Questionnaire, Which Is A Collection Of Data Through A List Of Questions Prepared For Each Respondent. Besides The Interviews Is Also DoneÂ  Sign Accountable To The Relevant Parties Within The Company Which Carried Out Systematically By Objective Research.The Method Of Analysis Used Is Multiple Linear Regression To View And Analyze The Factors That Influence Consumer Decisions In Choosing Handphone Flexi. The Results Of This Study Indicate That The Marketing Mix Factors Including Quality, Price, Distribution And Promotion Channels Simultaneously Or Jointly Have A Significant Influence On Consumer Decisions In Choosing Handphone Flexi. It Is Based On The Results Of The F Test Where Sig Is Less Than A = 5% Where The Value Of Each Variable Sig X1 (0.000), X2 (0.007), X3 (0.041), X4 (0.018).Thus The Assessment That Saying That The Alleged Each Variable Has A Significant Influence On Consumer Decisions In Choosing Handphone Flexi Accepted. Among The Independent Variables Studied, Showed That The Variable Quality Of The Card Has A Dominant Influence On Consumer Decisions In Choosing Handphone Flexi. It Is Based On T Test Results That Show That The Value Of The Coefficient Sig Card Quality Is Less Than A = 5%. Thus The Second Hypothesis Which States Alleged That The Variable Quality Of The Handphone Has The Most Dominant Influence Among All The Variables On Consumer Behavior In Choosing Handphone Flexi AtÂ  PT. Telecommunications Indonesia, Tbk Samarinda Received.